Effects of various irrigation and fertilizer on water efficiency and tomato yield (Solanum lycopersicum) in Alfisols - Rahayu Rahayu; Aktavia Herawati; Nur Faizaturrohmah (Universitas Sebelas Maret, 2021)
Investing in irrigation is very important and strategic in the context of water supply for agriculture. Therefore, this study aims to identify the most efficient irrigation technique and type of fertilizer to maximize the yield of tomatoes (Solanum lycopersicum) in Alfisols. This study was a greenhouse pot experiment with a factorial completely randomized design with two factors consisting of four irrigation techniques (pottery, drip, 75% ETc manual, and 100% ETc manual) and types of fertilizers (without, organic, inorganic, mixed fertilizer). The results showed that pottery irrigation had the highest Nitrogen content in the soil and saved up to 50% water compared to 100% ETc. On the other hand, drip irrigation uses water of 75% ETc with similar plant yield results. The pottery irrigation was the most efficient irrigation method for growing tomato than 75% ETc manual irrigation, and 100% ETc manual irrigation with mixed fertilizers (I4P3) was the highest on tomato yield.